Kesejahteraan Tenaga Pendukung: Perspektif Regulasi Ketenagakerjaan di Sekretariat DPRD Provinsi Kepulauan Riau - Reindra, Nanda; Nurlaily (Unram Law Review, 2025)
The welfare of support workers plays a crucial role in ensuring efficient public service delivery, particularly within governmental institutions such as the Secretariat of the Regional People’s Representative Council (DPRD) of Riau Islands Province. This study examines the welfare conditions of support workers through the lens of labor regulations, analyzing the extent to which existing policies provide adequate protection, fair wages, job security, and social benefits. By employing a normative juridical approach and qualitative analysis, this research explores the alignment between local labor policies and national laws, identifying gaps and challenges in implementation. Findings indicate that while Indonesia's labor regulations provide a legal framework for worker welfare, practical enforcement remains inconsistent, often resulting in wage disparities, contractual employment terms, and access to social security benefits for support staff. The study highlights the need for policy adjustments and stricter regulatory oversight to enhance the welfare of support workers in government institutions. Recommendations include strengthening legal enforcement improving contractual protections, and promoting equitable labor policies to ensure fair treatment and sustainable livelihoods for support workers.